Comparative Study on Serum Hepatic Enzymes between Normal Healthy Adults and Obese People of Rajshahi City (Ibrahim Cardiac Medical Journal, 2022)
Background & objective: Obesity is rapidly emerging as one of the major causes of non-alcoholic fatty liver disease (NAFLD), the early sign of which is elevated liver enzymes. But very few studies have yet been done in our country to find the association between overweight and obesity and levels of serum hepatic enzymes. The present study was undertaken to determine the association between overweight/obesity determined by body mass index (BMI) and serum hepatic enzymes.Methods: This cross-sectional analytical study was conducted in the Department of Physiology, Rajshahi Medical College, Rajshahi over a period of one year between July 2018 to June 2019 in collaboration with the Department of Biochemistry of the same Medical College. Based on certain predefined enrolment criteria, 33 overweight or obese (BMI ≥23 kg/m2) individuals (case) and 33 sex-matched apparently healthy adults (BMI